Determination of Volatile Compounds in Foxtail Millet Sake Using Headspace Solid-Phase Microextraction and Gas Chromatography-Mass Spectrometry - Jingke Liu; Wei Zhao; Shaohui Li; Aixia Zhang; Yuzong Zhang; Songyan Liu (Journal of Chemistry)
The volatile compounds in foxtail millet sake were extracted by headspace solid-phase microextraction (HS-SPME) and analyzed using gas chromatography-mass spectroscopy (GC-MS). Different methods of sample preparation were used to optimize this method (SPME fiber types, sample amount, extraction time, extraction temperature, content of NaCl, and rotor speed). For final method of sample preparation, 8 mL of sake was placed in a 15 mL headspace vial with addition of 1.5 g of NaCl; a 50/30 μm DVB/CAR/PDMS SPME fiber was used for extraction at 50°C for 30 min with 10 rpm continuous stirring. A total of 41 volatile compounds were identified from the sake sample, including 9 esters, 6 alcohols, 4 acids, 4 aldehydes, 9 hydrocarbons, 7 benzene derivatives, and 2 others. The main volatile compounds were ethyl acetate, phenylethyl alcohol, butanedioic acid diethyl ester, and hexadecane. According to their odors active values (OAVs), 10 volatile compounds were established to be odor active compounds and to contribute to the typical foxtail millet sake aroma. Hexanoic acid ethyl ester was the most prominent odor active compound.